Is the Use of the Extended (Meth)acrylate Series – Nails Justified? Characterization of Nail Acrylate Allergy in a Tertiary Medical Centre - Joel Dascalu; Sophia Polansky; Ziad Khamaysi; Emily Avitan-Hersh; Mariela J. Nevet (Acta Dermato-Venereologica)
Methacrylate allergy is a common cause of allergic contact dermatitis, and its incidence has surged over the past decade. Consequently, the primary sensitizing agent, 2-hydroxyethyl methacrylate, was recently added to the European Baseline Series of contact allergens. This study aimed to assess the added value of testing for allergens included in the (Meth)Acrylate Series – Nails, in addition to 2-hydroxyethyl methacrylate, as well as to characterize patients who may benefit from more extensive testing. A retrospective analysis of medical records of patch-tested patients was conducted between June 2013 and July 2022. Among the 3,828 patients who underwent patch testing, 396 were tested with the (Meth)Acrylate Series – Nails; 153 (38.6%) of those patients tested positive for at least 1 acrylate. The most common hapten was 2-hydroxyethyl methacrylate (85.6%), followed by hydroxypropyl methacrylate (85.0%) and ethylene glycol dimethacrylate (80.4%). In our study, 22/153 patients (14.4%) would have been missed if tested only for 2-hydroxyethyl methacrylate. The analysis showed that including hydroxypropyl methacrylate and ethylene glycol dimethacrylate improved detection rate to 98%, rendering the use of the entire tray unnecessary in most cases.